The Orchard Secret : Arden Blake Mystery Series #1 - Garis, Cleo F., 1905-1998 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Orchard Secret" by Cleo F. Garis is a mystery novel written in the early 20th century. The book centers around three college freshmen, Arden Blake, Terry Landry, and Sim Westover, as they embark on their new lives at Cedar Ridge College. The narrative introduces a mysterious orchard on campus and hints at strange occurrences and a deeper secret, setting the stage for the girls' adventures and challenges as they navigate college life and their unexpected encounters with danger. The opening of the story follows Arden, Terry, and Sim as they arrive at Cedar Ridge College, eagerly anticipating their new experiences. Soon after their arrival, a taxi driver warns them about the orchard, claiming that "queer things" happen there. As the girls explore their surroundings, they learn the swimming pool has been repurposed for storage, disappointing their hopes for recreation. Following a series of light-hearted interactions and the exploration of their shared dorm room, they find themselves embroiled in the freshmen hazing rituals led by the sophomores, which includes a daunting task of gathering perfect apples from the orchard. As they begin this mission, they encounter a shocking discovery that hints at the hidden dangers lurking within the seemingly serene college grounds. (This is an automatically generated summary.)
Release date is 2012-09-10
E-text prepared by Stephen Hutcheson, Dave Morgan, and the Online Distributed Proofreading Team
Keywords: Friendship -- Juvenile fiction; Young women -- Juvenile fiction; Mystery and detective stories; Hazing -- Juvenile fiction; Women college students -- Juvenile fiction